Spatial Analysis of Available and Suitable Land for Oil Palm in Ketapang Regency - Yuwono, Probo; Widiatmaka, Widiatmaka; Fuah, Asnath Maria (JOURNAL OF TROPICAL SOILS, 2025)
Oil palm plantations are a primary sub-sector of Indonesia’s agricultural economy and continue to expand rapidly. Ketapang Regency, which has the largest oil palm plantation area in West Kalimantan, holds significant potential for further development. This study assessed land suitability for oil palm expansion using a Multi-Criteria Decision-Making approach integrated with Geographic Information Systems. The Analytical Hierarchy Process was applied to assign weights to the following criteria: slope, land cover, spatial pattern, soil texture, adequate depth, drainage, temperature, rainfall, and road accessibility. The results show that 79.56% of the total area is classified as suitable (S1 and S2), comprising 3.17% as highly suitable (S1) and 67.11% as suitable (S2). Meanwhile, 7.62% was moderately suitable (S3) and 20.44% was not suitable (N). Overlay analysis revealed that the most suitable lands overlap with Other Use Areas and Conversion Production Forests, while some intersect with existing agricultural and plantation uses. Validation with existing plantation data confirmed that 98.34% of plantations are located in S1 and S2 zones, demonstrating the robustness of the model. Overall, Ketapang Regency has substantial land availability for oil palm expansion. However, the limited extent of highly suitable land (S1) and the predominance of suitable (S2) highlight the need for cautious interpretation of expansion opportunities. Sustainable development must align with spatial regulations, land conversion policies, and environmental safeguards. Future research should integrate socio-economic, ecological, and climate change considerations to support sustainable and resilient oil palm development.